Subsidization of the Fund's Emergency Assistance for Natural Disasters to PRGF-Eligible Members. (Policy Papers; Policy Paper, 2005)
This paper provides the semi-annual update on the financing of PRGF and HIPC operations and the subsidization of post-conflict emergency assistance.